Sequential infusion of donor‐derived dendritic cells with donor lymphocyte infusion for relapsed hematologic cancers after allogeneic hematopoietic stem cell transplantation. Issue 12 (27th August 2014) - Ho, Vincent T.; Kim, Haesook T.; Kao, Grace; Cutler, Corey; Levine, James; Rosenblatt, Jacalyn; Joyce, Robin; Antin, Joseph H.; Soiffer, Robert J.; Ritz, Jerome; Avigan, David; Alyea, Edwin P.
<x xml:space="preserve">Abstract</x> Donor lymphocyte infusion (DLI) is often given to induce a graft‐versus‐leukemia (GVL) effect after allogeneic hematopoietic stem cell transplantation (HSCT). However, efficacy of DLI is limited in most hematologic cancers. As antigen presenting cells, dendritic cells (DC) bolster immune responses. We conducted a Phase I trial testing the coinfusion of DC followed by DLI. DC were generated by culturing peripheral blood mononuclear cells from HLA matched‐related donors in GM‐CSF and IL‐4 for 7 days, followed by TNF‐α for 3 days. DC were administered intravenously on 3 dose levels (5 × 106; 1 × 107; 5 × 107 cells). DLI (3 × 107 CD3+ cells/kg) was administered intravenously 1 day after the DC. Sixteen patients with hematologic cancers relapsed after HSCT were treated. A maximum tolerated dose for DC was not reached. Two of 16 patients met criteria for DLT within 10 weeks of the infusion: 1 idiopathic respiratory failure, 1 ventricular cardiac arrest. None developed grade III/IV GVHD. One patient developed grade II acute intestinal graft‐vs.‐host disease (GVHD) and 1 chronic GVHD within 6 months of the infusion. Both resolved with corticosteroids. Four of 14 patients evaluable for disease response achieved durable remissions and are alive and cancer free 6.7, 8.4, 8.8, and 10.1 years from infusion. Sequential infusion of donor‐derived DC with DLI is feasible in patients with relapsed hematologic cancers after allogeneic HSCT. Future studies may consider donor DC preloaded with tumor antigens to investigate whether DC infusion could augment the GVL effect. Am. J. Hematol. 89:1092–1096, 2014. © 2014 Wiley Periodicals, Inc.